Cooperação e solidariedade em empreendimentos de economia solidária - Vanessa Andrade de Barros; Fabiana Goulart de Oliveira (Universidade do Porto, 2019)
This research analyzes how cooperation links are formed, how solidarity mediates them and their importance to guarantee efficiency in solidarity economy initiatives. These initiatives are defined by collective ownership of the means of production, despite being inserted in a capitalist system. Mediating the relationship between solidarity and cooperation, in this case, becomes specific and conflicting. This project is based on conceptual elements and analytical data. The latter was obtained from empirical research in the sector of recyclable materials sorting of two solidarity economy initiatives. The present work utilizes both sources to understand the operative modes and strategies developed to regulate activities in the cooperative. In addition, the study analyzes how the companies consider the singularities and different work capacities since the activity imposes the same speed for all female workers. The conclusion is that cooperation is essential for constructing specific types of teamwork and for establishing solidarity sociabilities.